Mapping governance of adaptation to climate change in Switzerland - Dominik Braunschweiger (Regional Studies, Regional Science, 2018)
Climate change severely affects Alpine regions. Adaptation to climate change is needed in order to deal with these impacts, but the implementation of national adaptation strategies is inhibited by multiple obstacles. Regional strategic frameworks are just emerging, adaptation is of little priority to local agendas and policy mainstreaming is limited on all administrative levels. This paper provides a better understanding of the governance of adaptation to climate change in Switzerland, an example of a federal system with a strong focus on subnational levels and multilevel governance. We conceptualize governance as a network of policies, measures, actors and knowledge, and visualize their interactions using D3.js, a data-driven JavaScript library. The findings illustrate the typical division of labour in federal multilevel governance systems. The national level provides a strategic framework and funding and conducts coordinating measures at subnational levels, especially the local-level implementation of concrete measures. Conducting comparable mappings for other countries would allow interesting comparisons and insights into common barriers and opportunities to adaptation to climate change.